The effectiveness of studying foreign language in the intercultural communication - Kononenko Anna; Nedospasova Larisa (E3S Web of Conferences, 2021)
The variety of the intercultural communication provides the existence of different methods and tools that appear in learning process using the intercultural interaction in preparing future specialists. For understanding the intercultural communication it should be combined the knowledge and understanding another culture language. Moreover, the developing intercultural communication process should be seen in practice if the students have opportunities to develop language skills of the intercultural communication in daily routine or in professional situations conducted at the different learning classes with using modern pedagogical methods. One of the most effective ways of intercultural communication is a motivation to learn a foreign language for special occasions aimed at obtaining professional skills and professional experience. Achieving a high professional level of language training is directly related to the peculiarities of a foreign language culture. The proposed method is based on communicative competence of learners with practical implementation in the professional sphere. The method under consideration makes it possible to give conclusions about necessity for studying a foreign language and pay attention to filling the learning language content using professional direction. Nowadays, the professionals with high level of the foreign language in various fields are highly competitive and indispensable now. The obtained results of the research based on the effectiveness of modern methods` use and application in the classroom for preparing future specialists.